Synthesis and Docking Studies of the Novel N-(2,2-Di(1H-pyrrol-2-yl)ethyl)adamantane-1-carboxamide, a Potential 11β-HSD1 Inhibitor - Salvador Gallardo-Alfonzo; Ana Lilia Ocampo-Néstor; Claudia Contreras-Celedón; Luis Chacón-García (Journal of Chemistry)
The synthesis of the novel 1-adamantyl-(N-meso-dipyrrolylmethylene)-carboxamide is described, providing a three-step, two-pot reaction. Docking studies with 11β-HSD1 revealed favorable binding interactions with the enzyme.